2014
DOI: 10.1063/1.4869134
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Fermi level position in dilute magnetic Ga1-xMnxN films

Abstract: We report on a combined theoretical and experimental determination of the Fermi level position in wurtzite Ga 1−x Mn x N films with x = 4% and x = 10% as grown by molecular beam epitaxy. By means of ellipsometric measurements the real part of the frequency-dependent conductivity is determined. An electronic model in the framework of the effective bond-orbital model is parameterized in order to theoretically reproduce the measured transport properties. Predictions for the long-wavelength behaviour as a function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(49 reference statements)
3
1
0
Order By: Relevance
“…in a close proximity to the Mn-related band which is located between 1.4 to 1.8 eV above the valence band edge in (Ga,Mn)N 2,15,[37][38][39] . This conclusion is consistent with recent studies of the valency of Mn atoms in (Ga,Mn)N films which was found to be 2.4 eV 40 as well as with ellipsometric assessment of the Fermi level position in (Ga,Mn)N and corresponding theoretical calculations 41 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…in a close proximity to the Mn-related band which is located between 1.4 to 1.8 eV above the valence band edge in (Ga,Mn)N 2,15,[37][38][39] . This conclusion is consistent with recent studies of the valency of Mn atoms in (Ga,Mn)N films which was found to be 2.4 eV 40 as well as with ellipsometric assessment of the Fermi level position in (Ga,Mn)N and corresponding theoretical calculations 41 .…”
Section: Resultssupporting
confidence: 93%
“…This conclusion is consistent with recent studies of the valency of Mn atoms in (Ga,Mn)N films which was found to be 2.4 eV (ref. 40 ) as well as with ellipsometric assessment of the Fermi level position in (Ga,Mn)N and corresponding theoretical calculations 41 . Such conditions of the Fermi level position in (Ga, Mn)N are certainly very unfavorable for achieving the carrier mediated ferromagnetism in this material, at room temperature in particular, and they advocate strongly for the superexchange Mn 3+ - Mn 3+ coupling postulated in refs 10 , 12 to explain rather low temperature ferromagnetism in these samples.…”
Section: Resultsmentioning
confidence: 99%
“…The widening of the VB in the vicinity of the Fermi level follows from the subsurface layer's modification caused by the incorporation of Mn atoms, leading to the formation of a p-type (Mn)GaN-like alloy. This is in line with the literature [94][95][96], where it is shown that the Mn presence in the GaN matrix reconstructs the VB. Another reason that the VBM is practically located at the Fermi level may be surface-state deprivation and, thus, an elimination of band bending on GaN(0001).…”
Section: Mn On Gan(0001)supporting
confidence: 93%
“…The widening of the VB in the vicinity of the Fermi level follows from the subsurface layer's modification caused by the incorporation of Mn atoms, leading to the formation of p-type (Mn)GaN-like alloy. This is in line with the literature [94][95][96], where it is shown that the Mn presence in the GaN matrix reconstructs the VB. Another reason that the VBM is practically located by the Fermi level may be surface states deprivation and thus an elimination of band bending on GaN(0001).…”
Section: Mn On Gan(0001)supporting
confidence: 93%